Amulets and Talismans of the Middle East and North Africa in Context : Transmission, Efficacy and Collections - Probert, Marcela A. Garcia,; Sijpesteijn, Petra M., (Leiden Studies in Islam and Society ;, 2022)
In this volume amulets and talismans are studied within a broader system of meaning that shapes how they were manufactured, activated and used in different networks. Text, material features and the environments in which these artifacts circulated, are studied alongside each other, resulting in an innovative approach to understand the many different functions these objects could fulfil in pre-modern times. Produced and used by Muslims and non-Muslims alike, the case studies presented here include objects that differ in size, material, language and shape. What the articles share is an all-round, in-depth approach that helps the reader understand the complexity of the objects discussed and will improve one's understanding of the role they played within pre-modern societies. Contributors Hazem Hussein Abbas Ali, Gideon Bohak, Ursula Hammed, Juan Campo, Jean-Charles Coulon, Venetia Porter, Marcela Garcia Probert, Anne Regourd, Yasmine al-Saleh, Karl Schaefer and Petra M. Sijpesteijn.